1987
DOI: 10.1111/j.1476-5381.1987.tb08990.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental responses to opioids reveals a lack of effect on stress‐induced corticosterone levels in neonatal rats

Abstract: 1 The neonate has an unusual capacity for survival and the possibility exists that mechanisms for controlling stress responses may differ in the developing animal. In adults both endogenous and exogenous opioids can modulate the corticosterone responses to stress. We have studied this effect in neonatal rats and found that opioid modulation is absent in early postnatal development.2 Neonatal rats ofeither sex were injected with morphine (5-50mg kg-'), fentanyl (10-100 .tLg kg-'), buprenorphine (O.1-30 mg kg') … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Rodent studies have shown significant stressinduced activation of the HPA axis in neonatal rat pups, although sensitivity to stressors is reduced considerably after the first several postnatal days, with this stress hyporesponsive period (SHRP) lasting for most of the first 2 weeks of postnatal life [481]. While similar peak corticosterone responses to stressors have occasionally been observed in weanlings, adolescent and adult rats [23,82,202], stress-induced HPA activation has more consistently been reported to increase ontogenetically following the SHRP in rats to reach an asymptote around adolescence, at least in males [29,357,452,463,569,574]. In recent work using mice, however, adolescents were observed to have lower corticosterone levels than adults following the mild stress of saline injection [312].…”
Section: Hormonal Response To Stressors In Adolescencementioning
confidence: 99%
See 3 more Smart Citations
“…Rodent studies have shown significant stressinduced activation of the HPA axis in neonatal rat pups, although sensitivity to stressors is reduced considerably after the first several postnatal days, with this stress hyporesponsive period (SHRP) lasting for most of the first 2 weeks of postnatal life [481]. While similar peak corticosterone responses to stressors have occasionally been observed in weanlings, adolescent and adult rats [23,82,202], stress-induced HPA activation has more consistently been reported to increase ontogenetically following the SHRP in rats to reach an asymptote around adolescence, at least in males [29,357,452,463,569,574]. In recent work using mice, however, adolescents were observed to have lower corticosterone levels than adults following the mild stress of saline injection [312].…”
Section: Hormonal Response To Stressors In Adolescencementioning
confidence: 99%
“…In this regard, it may be highly significant that several studies have incidentally noted that adolescent rats exhibit lower drug-induced increases in plasma corticosterone levels than do their more mature counterparts. This paradoxically attenuated corticosterone response to drug exposure has been seen in adolescent rats following challenge with morphine [29], cocaine [313] as well as ethanol [497], and in adolescent mice following amphetamine [312]. To the extent that elevations in corticosterone contribute to the reward value of drugs, higher levels of adolescent drug exposure may be necessary to attain the reinforcing value that these drugs have in more mature individuals.…”
Section: Stress and Drug Abuse In Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, reminiscent of human adolescent behavior, adolescent rats are often hyperactive and explore more vigorously relative to rats of other ages (Spear et al, 1980). In addition, both human adolescents and adolescent laboratory rats show an enhanced hormonal and physiological response to stressors (Bailey and Kitchen, 1987;Meaney et al, 1985;Ramaley and Olson, 1974;Rivier, 1989;Walker et al, 1986Walker et al, , 1998. What makes these similarities interesting in the present context is other research that suggests that exploratory behavior and stress may be important factors involved in the tendency of human adolescents to drink heavily (Baer et al, 1987;Deykin et al, 1987;Pohorecky, 1991;Tschann et al, 1994;Wills, 1986).…”
Section: Pe E Er Er R Rs S Sp Sp P Pec Ec E Ec Cti Ti T Ti Ive Ve V Ve Ementioning
confidence: 99%